1978
DOI: 10.1159/000152994
|View full text |Cite
|
Sign up to set email alerts
|

Sequence of Action of Genes at the Secretor, H, ABO and Lewis Loci

Abstract: It is argued that Lewis genes are responsible for adding specificity to glycol-protein molecules after the activities of the secretor, H and ABO genes, respectively, have been expressed. This conclusion is based on the results of studies on the expression of ABO and Lewis antigens in salivas from Australian aborigines, and on biochemical results. A simple figure illustrating the antigens determined on red cells and in body secretions as a result of the action of these genes, in their correct order – secretor, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
1999
1999

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Watkins (1959), Watkins and Morgan (1959) and Ceppellini (1959) Lewis substances was secreted. The investigations made by these and other workers which followed showed that the genes were more likely to act in the order Sese, Hh, ABO and Lele (Boettcher, 1978), but the possibility apparently also exists that independent recessive suppressor genes inherited in double dose may alter the a-2-L-fucosyltransferase expressed by normally-inhertied H genes in 0h individuals (Watkins, 1980).…”
Section: Discussionmentioning
confidence: 89%
“…Watkins (1959), Watkins and Morgan (1959) and Ceppellini (1959) Lewis substances was secreted. The investigations made by these and other workers which followed showed that the genes were more likely to act in the order Sese, Hh, ABO and Lele (Boettcher, 1978), but the possibility apparently also exists that independent recessive suppressor genes inherited in double dose may alter the a-2-L-fucosyltransferase expressed by normally-inhertied H genes in 0h individuals (Watkins, 1980).…”
Section: Discussionmentioning
confidence: 89%
“…The presence of the antigens in aqueous body fluids, a dominant genetically controlled character, depends on the synthesis of the H antigen. In non-secretors, the H antigen is not synthesized and, although the A or B genes may be active, little A or B antigen is expressed (2).…”
Section: Introductionmentioning
confidence: 99%